Characterization of the Secondary Neutron Field Produced in a Thick Aluminum Shield by 1 GeV/u 56Fe Ions Using TLD-Based Ambient Dosimeters - Boscolo, Daria; Scognamiglio, Daniela; Horst, Felix; Weber, Uli; Schuy, Christoph; Durante, Marco; La Tessa, Chiara; Kozlova, Ekaterina; Sokolov, Alexey; Dinescu, Irina; Radon, Torsten; Radeck, Désirée; et al. (Frontiers in Physics, 2020)
The neutron ambient dose equivalent induced by galactic cosmic ray-like (1 GeV/u 56Fe) radiation stopped in a thick aluminum shield was measured at different angles with GSI neutron ball, the standard TLD (thermoluminescent dosimeters) based neutron dosimeter for area monitoring at the GSI facility. In order to measure reliably at large angles, a modified version of the GSI ball, including a set of three more sensitive TLD600H/700H cards, instead of one standard TLD600/700, cards was used. The modified GSI balls were calibrated in neutron reference fields of 241Am-Be(alpha,n) available at the Physikalisch-Technische Bundesanstalt (PTB). The neutron ambient dose equivalent was measured at 5 different angles (15, 40, 90, 115 and 130 degree) with respect to the beam direction and compared to the calculated detector response and ambient neutron dose equivalent results from FLUKA simulations. The dosimeter readings were corrected for signal contributions coming from secondary charged particles. An agreement within 15 % was found between the measured and calculated GSI ball response and an agreement within 30 % was found between experiments and calculated neutron dose equivalents.